Evaluation of the Role of Commercial Banks in Supporting and Promoting Financial Inclusion in Algeria during the Period 2014-2020 - Houssni, Baali (Finance and Business Economies Review, 2022)
This study aimed to highlight the reality of financial inclusion in Algeria in comparison with the countries of the world, by addressing its most important indicators related to the use of bank accounts, savings, borrowing and making payments, as well as an attempt to evaluate the efforts of financial and banking institutions in supporting and enhancing levels of financial inclusion, Problems and challenges that face it in Algeria. The study concluded that Algeria has generally achieved medium levels of financial inclusion, as it recorded low rates of saving and borrowing from official financial institutions, despite the improvement recorded in the rates of owning bank accounts and settling payments, which is mainly due to the efforts of financial and banking institutions in Expanding its networks to all regions of the country, spreading awareness and financial culture, as well as providing various financial products that respond to the needs of customers and all members of society, especially digital banking services. There is also an urgent need to adopt a national strategy for financial inclusion, where the banking sector has a great responsibility to promote and raise its levels.